ANALISIS PENGARUH KARAKTERISTIK CURAH HUJAN TERHADAP KERUNTUHAN LERENG DENGAN MENGGUNAKAN APLIKASI GEO SLOPE (Studi Kasus : Jalan Simalaka (Sicincin-Malalak-Balingka) - Nofrizal Nofrizal; Amelia Yulastri; Febi Silvia Deni (Ensiklopedia of Journal, 2021)
Avalanches are a frequent event on a slope. One of the important factors that causes landslides in addition to the load that is on the slopes is the infiltration of rainwater. In the rainfall data in malalak road area also has the intensity of rain with heavy rainfall conditions. Not closing is likely to be a avalanche. This research was conducted to analyze the amount of safety figures on Malalak Road. This study is classified into applied research. Kajian will use soil parameter data and rainfall data,, as compare the safe factors obtained using fellenius medote and Geo-studio V Software, due to disturbed soil stability or slope building rocks. Analysis of the use of the Geo-Studio program and using the Fellenius method showed the safety factor value of the slopes in the Malalak area was0.80. Therefore the result itu means the slopesin kalert are inunstable condition because it has a safety factoran < 1,5 . The analysis of calculations from research conducted on malalak road section KM 28 shows that the value of safety factors obtained is still said to be labil, where the value of FK is less than 1.5 can be concluded that the infiltration of rain and slope slope is very influential to the stability of the slope. Dimana safety factor or FK (Safety Factor) slope decreases along with the length of rainwater infiltration that occurs in malalak area.